Canadian science, technology, and innovation policy the innovation economy and society nexus - Doern, G. Bruce 1942-; Castle, David 1967-; Phillips, Peter W. B. (McGill-Queen's University Press, 2016)
"Throughout Science, Technology, and Innovation Policy in Canada since 1960, authors Doern, Castle, and Phillips examine Canadian science and technology (S & T) and innovation policy (STI policy), governance and democracy in the post-World War II era--particularly focusing on the five decades during the Harper, Chrétien-Martin, Mulroney, and Trudeau prime-ministerial eras. They attempt to develop and advance the concept of an innovation economy and society nexus and understand whether, and to what extent, the current concerns raised about Canadian STI policy are new, or are embedded and long-standing, and whether they can be changed and reformed to achieve other, more defensible goals in private markets and the public domain. Doern, Castle, and Phillips focus their investigation on three principal questions: 1) How, why, and to what extent Canadian S & T and innovation policy, governance, and democracy have changed over the last 50 years, 2) Where S & T and innovation policy resided in Canadian federal political and policy agendas across the last 50 years, and 3) How concepts of science-based governance prevailed or been changed across the last several decades."--
Keywords: Geschichte 1900-2000; Science and state / Canada / History / 20th century; Science and industry / Government policy / Canada / History / 20th century; Technology and state / Canada / History / 20th century; Technological innovations / Government policy / Canada / History / 20th century; Science and industry / Government policy; Science and state; Technological innovations / Government policy; Technology and state; Geschichte; Politik; Föderalismus; Wissenschaft; Innovation; Gemeinwohl; Technologie; Canada; Kanada